THE DECONSTRUCTION OF MYTH LIKE THE SEARCH FOR IDENTITY: (Based on Amy Tan’s Novel “The Kitchen God's Wife”) - Nigar Rauf Asgarova (International Journal of Innovative Technologies in Social Science, 2022)
The article examines the identity of a Chinese-American woman in the novel “The Kitchen God’s Wife” by modern American writer A.Tan in parallel with the “Kitchen God”, one of the ancient Chinese myths. It turns out that A.Tan deconstructs the plot line from Chinese mythology against the background of the life story of modern man and presents this image as a woman of the new world. This woman behaves and lives like a man of the modern world, along with her roots, customs, and traditions. A.Tan deconstructs the image of a woman belonging to the mythical world and, unlike Chinese myths, describes her not as submissive and obedient, but as a real-world woman who fights for her rights and understands her national identity. The writer brings the mythical thought to the level of problems of the modern world and evokes ideas about the Chinese-American's national identity, its past, and its essence. E.Tan refers to images and motifs taken from Chinese mythological and folklore sources, preferring Chinese cultural symbols. Highlighting the ethnic past, E.Tan warns that every Chinese is bound to lose as well as gain in the contact of cultures. For this reason, he deconstructs the myth of the "Kitchen God” to reconsider the national moral bonds in the novel "The Kitchen God's Wife".